2018
DOI: 10.3390/ma11101807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pr and Yb Dual Doping on the Thermoelectric Properties of CaMnO3

Abstract: There has been research on CaMnO3 with natural abundance, low toxicity, and low cost as promising candidates for n-type thermoelectric (TE) materials. In this paper, Ca1−2xPrxYbxMnO3 with different Pr and Yb contents (x = 0, 0.01, 0.02, 0.03, 0.04 and 0.05) were synthesized by means of coprecipitation. With X-ray diffraction (XRD), scanning electron microscopy (SEM), and high-resolution transmission electron microscopy (HRTEM), researchers characterized the phase structure and morphology of all the samples. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
2
9
1
Order By: Relevance
“…where k B is the Boltzmann constant and n and m* refer to the carrier concentration and the effective mass of the carrier, respectively. Snyder and Toberer 1 and Li et al 66 concluded that materials with low charge carrier concentration present as consequence high Seebeck coefficients values and low electrical conductivities, as also observed in this study. Srivastava et al 67 , observed in SrTiO 3 ceramics the reduction of the Seebeck coefficient and the increase in electrical conductivity with the increase of the sintering time.…”
Section: Resultssupporting
confidence: 83%
“…where k B is the Boltzmann constant and n and m* refer to the carrier concentration and the effective mass of the carrier, respectively. Snyder and Toberer 1 and Li et al 66 concluded that materials with low charge carrier concentration present as consequence high Seebeck coefficients values and low electrical conductivities, as also observed in this study. Srivastava et al 67 , observed in SrTiO 3 ceramics the reduction of the Seebeck coefficient and the increase in electrical conductivity with the increase of the sintering time.…”
Section: Resultssupporting
confidence: 83%
“…There is also a metal-insulator transition at high temperature due to a change in the spin state of Mn ions. Substituting Ca with heavy rare earths has been particularly successful in reducing thermal transport [613]; dual doping on both Ca and Mn sites can also enhance charge transport [614,616]. Theoretical work suggests that zT max of greater than 1.0 can be achieved in CMO [670], but to date the use of soft chemistry processing to develop sub-micron grains with nanosized twinned domains, has produced the best performing CMO with a zT max of 0.32 at 1060 K [613].…”
Section: Oxide Thermoelectricsmentioning
confidence: 99%
“… ( a ) p -Type; ( b ) n -type type-I Ioffe plots; ( c ) p -type; ( d ) n -type type-II Ioffe plots and ( e ) p -type and ( f ) n -type zT -electrical conductivity plots for several doped oxidic thermoelectric materials and BiCuSeO [ 10 , 11 , 39 , 69 , 74 , 80 , 96 , 102 ]. Dashed lines show the corresponding absolute values of the Seebeck coefficient given in V K −1 .…”
Section: Figurementioning
confidence: 99%